2012
DOI: 10.5993/ajhb.36.5.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 4 Recruiting Strategies in a Smoking Cessation Trial

Abstract: Objectives To compare 4 on-line and off-line recruiting methods. Methods Young adult smokers (n=3353) were recruited to a trial comparing smoking cessation services with an on-line health risk assessment (HRA), on-line ads, off-line materials, and quit line screening. Results On-line ads (n=1426; $41.35) and off-line materials recruited the most smokers (n=1341; $56.23) for the lowest cost. Quit line screening was more expensive (n=189; $133.61), but enrollees used cessation services the most (34%-82%). On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 23 publications
3
40
0
Order By: Relevance
“…Facebook was another lower cost approach with respect to cost per recruited smoker. Our findings about cost are consistent with past research showing that web-based advertisements are lower cost than other methods [15,17,18]. For instance, Ramo and colleagues found that Craigslist was particularly low cost per eligible smoker (<$1), although the researchers did not report cost per enrolled participant [18].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Facebook was another lower cost approach with respect to cost per recruited smoker. Our findings about cost are consistent with past research showing that web-based advertisements are lower cost than other methods [15,17,18]. For instance, Ramo and colleagues found that Craigslist was particularly low cost per eligible smoker (<$1), although the researchers did not report cost per enrolled participant [18].…”
Section: Discussionsupporting
confidence: 90%
“…For instance, Ramo and colleagues found that Craigslist was particularly low cost per eligible smoker (<$1), although the researchers did not report cost per enrolled participant [18]. Past studies have found that Craigslist is lower cost than Google Adwords, which may cost between $41 and $51 per enrolled smoker [15,16]. Newspaper ads, bus ads, and staff in-person recruiting were all relatively expensive and less effective at recruiting smokers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such methods include e-mailing members of a closed network who have agreed to be contacted (Temple and Brown, 2011), posting recruitment information on blogs or message boards (Riggle et al, 2005), purchasing website banner advertisements (Bull et al, 2008; Buller et al, 2012) or pop-up windows on websites frequented by members of the target population (Graham et al, 2006), and issuing electronic coupons to key informants who have agreed to assist in implementing online respondent-driven sampling (Evans et al, 2011). When employing offline recruitment methods, quick response (QR) codes can supplement online efforts by providing members of the target population with a link to the study website or social media page (Buller et al, 2012). The challenge with employing multiple recruitment methods is that the research team frequently loses the ability to have a defined sampling frame and to assume homogeneity within the sample.…”
Section: Introductionmentioning
confidence: 99%
“…In tailoring messages specific to the format and the audience, researchers may more readily establish rapport with the participants and gain their trust (Hershberger et al, 2011; Riggle et al, 2005; Temple and Brown, 2011). A combination of recruitment efforts may also be used (Temple and Brown, 2011), including combining with offline methods (Cook et al, 2009; Gordon et al, 2006; Hershberger et al, 2011; McClure et al, 2006; Parsons, Vial, Starks, & Golub, 2013), recruiting via message boards or blogs (Riggle et al, 2005), or targeting website advertisements to sites frequented by the intended participant population (Graham et al, Bull, Vallejos, Levine, & Ortiz, 2008; Buller et al, 2012; 2006). Participants may also be solicited using closed email networks of willing contacts (Temple and Brown, 2011) or by offering incentives to key informants who may in turn help drive online sampling (Evans et al, 2011).…”
Section: Introductionmentioning
confidence: 99%